Reading Proficiency Of Islamic Education Student In English For Islamic Studies [Case Study At STAIN Pekalongan] - RIZKINANTI (Jurusan Tarbiyah-Pendidikan Agama Islam- STAIN Pekalongan, 2012)
If we want to discover the knowledge, we have to begin to learn the language, because that comes first is knowledge and language reflects it. Implicitly, there is a verse in the Holy Quran suggesting us to learn foreign language. One of them is QS. Al Hujuraat: 13 that describes about nations and tribes. From the verse above, we know that from the diversity of clan and nation we need a language to communicate in order to know each other. Therefore, we have to know and understand a language that is known by majority people all over the world. In this case is an international language, English. By mastering an international language, mutual understanding will be realized in this global era.Reading in English in the context of Islamic studies is a part of English for Specific Purpose to enrich Muslims knowledge about Islam in English. It is learned by Islamic college students in their English class. The problem of the study is {how is the Reading Proficiency of Islamic Education Student of STAIN Pekalongan in English for Islamic Studies?}. The objective of the study is analyzing Islamic Education Study Program Student reading proficiency in English in the context of Islamic studies. Especially, for the Islamic Education students on the English 3 level.Theoretically, the study gives the description about reading proficiency ofIslamic Education student.Practically, the students of Islamic Education will be able to expand their capability in reading English text especially in the context of Islamic studies effectively whether they are in class or in daily life, it will become a recommendation in teaching Islamic Education classes because by knowing students’ ability in reading Islamic text and will give suggestions to STAIN Pekalongan as an Islamic college that is growing to develop the quality of its students. The design of this study is case study design. Case study is an appropriate research method when an investigator is trying to attribute causal relationship--and not just wanting to explore or describe a situation. Rather than generalizing to a universe or population, case study research should be used to expand our understanding of theoretical proposition and hypotheses those situations where (a) the context is important and (b) an investigator cannot manipulate events. The approach of this research is quantitative approach that is an approach in conducting a research by emphasizing on numerical analysis on statistic method. As a result, there is no student (0 %) gets good nor very good score. However, 19 students (50 %) get enough score, 17 students (45 %) get poor score, and unfortunately, there are 2 students (5 %) failed the test. According to the score frequency on each part, it can be said that the students of Islamic Education Tarbiyah Department in comprehending the reading text is good (39%), mastering vocabulary is failed (30%), using grammar is enough (47%). In summary, based on total score frequency above, can be claimed that the Islamic Religious Students reading proficiency on STAIN Pekalongan is enough since there is 50% of respondents (19) get enough score. Based on the research findings, the students had better to improve their English skills especially their vocabulary in the context of Islamic studies since studying English contextually is really important. Students can expand their reading proficiency through applying reading activities inside and/or outside the class such as learning and discussing with their peers.